Sensitivity analysis for the symplectic QR factorization. Issue 5 (March 2016) - Li, Wen; Xie, Ze-Jia; Vong, Seak-Weng
Abstract: In this paper, we give the sensitivity analysis for an implicit Bunch form of the symplectic QR factorization. In particular, we present some new first order normwise perturbation bounds for R - and Q -factors and propose the normwise condition numbers appropriately for two factors. Some numerical examples are given to demonstrate the theoretical results.